Competitive analysis of crude palm oil (CPO) in West Sumatera Province to other provinces in Sumatera Island in domestic market. Issue 1 (October 2020) - Nesti, L; Tan, F; Hadiguna, R A
Abstract: The agricultural sector in Indonesia, especially Crude Palm Oil (CPO) has contributed the country's foreign exchange with the value of CPO exports in 2016 amounting to the US 17.8 billion, up 8 per cent compared to the previous year of US IG.5 billion. This has led Indonesia to become the largest producer and exporter of palm oil until now. Six provinces became the largest production centre of palm oil in Indonesia, but West Sumatera Province has not been included in the big six. West Sumatera Province, which is still dominated by an agriculture sector, and or plantation sub-sector has contributed 6.57%. The purpose of this research is to analyze the competitiveness of CPO export of five provinces located in Sumatra Island in a domestic market and compare it with C PO competitiveness in West Sumatera Province with time-series data from 2000-2016 using RCA (Revealed Comparative Advantage) Index. The results show that on average the RCA value produced by RCA > 1 is only South Sumatera province with RCA < 1 if each year the analysis of each Province shows fluctuating RCA values that lend to show a decline. Except for the value of RCA Provinces West Sumatera showed on the increase. One of the causes of the declining RCA values is that each Province has started to focus on the development of downstream CPO products so that the CPO that was once more exported overseas has gradually started to reduce exports and more to meet domestic demand as raw materials CPO downstream products such as the manufacture of food and non-food products. Meanwhile, CPO in West Sumatera Province is still dominated by foreign exports compared to downstream development.